POLITICAL DEVELOPMENT IN SOUTHEAST ASIA: THE REFLECTION OF “FREEDOM IN THE WORLD” INDEX BY FREEDOM HOUSE ORGANIZATION - Yeedum, Maneroo (PEOPLE: International Journal of Social Sciences, 2015)
This research aims to understand and compare the significance of political development in Southeast Asia countries through democratic index, “Freedom in the World”, by Freedom House Organization. The study started with a consideration of “Freedom in the World” survey data from years cover 1972-2014 in 11 Southeast Asia countries. Then, explicated the substantial political phenomenon from the trends of data. The findings suggested that there are three clusters of political development in Southeast Asia. The First cluster is the countries which are designated to the one and only status every year of the Freedom House surveys: Burma, Vietnam, East Timor and Singapore. The Second cluster is the countries which are designated to two statuses in the periods of the Freedom House surveys: Brunei, Cambodia, Laos, Malaysia and the Philippines. The Third cluster is the countries which are designated to three statuses in the periods of the Freedom House surveys: Indonesia and Thailand.